Effect of tracked and rubber-tyred logging machines on soil physical properties of the Berkelah Forest Reserve, Malaysia - Kamaruzaman Jusoff (2023)
Wheel and track traffic of heavy forest machinery is causing increased concern about forest soil compaction. Compared to agriculture, forest mechanization is potentially more damaging to site productivity because forestry machines tend to be heavier and operations are performed throughout the year regardless of weather conditions. Field experiments of vehicular compaction tests were initiated in dry and wet months (June and November, respectively) on a clay loam soil at the Berkelah Forest Reserve in central Pahang, Malaysia. Two unloaded tree harvesting (TH) machine types (crawler tractor and rubber-tyred loader), two soil moisture contents (14 and 21 % of oven dry weight) and vehicular trips (0,1,2, 4, 8,16, 32 and 50 passes) were assessed on soil conditions from 0 to 15 cm depth. Rates of soil degradation are very different for the two machines. Changes in soil dry bulk density (DBD), total pore space (TPS), aeration porosity (AP), available water-holding capacity (AWC), saturated hydraulic conductivity (SHC) and resistance to penetration (RP) of the rubber-tyred tractor did not exceed those caused by a track-type crawler tractor despite a two-fold difference in mean ground contact pressure. The changes in soil DBD and TPS caused by both machines increased with increasing soil moisture content. However, AP, AWC, SHC and RP decreased with increasing soil moisture content. Most soil physical properties studied reached a maximum or minimum after the first two passes and remained constant thereafter with the tyred machine. SHC appears to be the most sensitive parameter for machine differences. Effects of heavy machinery operation on surface soil compaction should be recognized in forest mechanization.